The development of biology comic to enhancement analytical thinking skill and adolescent reproductive health knowledge - Wardhani, I. Y.; Melisa, A. O.; Fauzia, F. E. A.; Laelasari, I.; Jalil, M. (AIP conference proceedings, 2023)
This study aims to reveal 1) the advisability of biology comic media; 2) the effect of biology comic media on students’ analytical thinking skills; 3 the knowledge of adolescent reproductive health after the using biology comic media. The study was a research and development study which referred to the model suggested by Thiagarajan. The design of the study consisted of four developmental procedures which are (a) defining, (b) designing, (c) developing, (d) disseminating. The products of this study is Bio-Comic Media with material human reproductive system. The subjects of the study were the second grade students of MA Zumrotul Wildan Jepara. The field testing subjects consisted of 28 second grade students of IPA as the experimental class. The data were collected using a documentation, observations, and tests. The results of the study show that the biology comic media were categorized as valid, and effective, based on the experts’ judgement and students’ assessments. Hypothesis test results reveal that biology comic media affects the students’ analytical thinking skills with sig value=0.00 (Wilcoxon test). The number of students who have Adolescent Reproductive Health (ARH) knowledge minimum of "Good" is 70% or as many as 20 students, with mean score is 83.